Tissue‐selective expression of a conditionally‐active ROCK2‐estrogen receptor fusion protein. Issue 12 (8th November 2016) - Samuel, Michael S.; Rath, Nicola; Masre, Siti F.; Boyle, Sarah T.; Greenhalgh, David A.; Kochetkova, Marina; Bryson, Sheila; Stevenson, David; Olson, Michael F.
Abstract: The serine/threonine kinases ROCK1 and ROCK2 are central mediators of actomyosin contractile force generation that act downstream of the RhoA small GTP‐binding protein. As a result, they have key roles in regulating cell morphology and proliferation, and have been implicated in numerous pathological conditions and diseases including hypertension and cancer. Here we describe the generation of a gene‐targeted mouse line that enables CRE‐inducible expression of a conditionally‐active fusion between the ROCK2 kinase domain and the hormone‐binding domain of a mutated estrogen receptor (ROCK2:ER). This two‐stage system of regulation allows for tissue‐selective expression of the ROCK2:ER fusion protein, which then requires administration of estrogen analogues such as tamoxifen or 4‐hydroxytamoxifen to elicit kinase activity. This conditional gain‐of‐function system was validated in multiple tissues by crossing with mice expressing CRE recombinase under the transcriptional control of cytokeratin14 ( K14 ), murine mammary tumor virus ( MMTV ) or cytochrome P450 Cyp1A1 ( Ah ) promoters, driving appropriate expression in the epidermis, mammary or intestinal epithelia respectively. Given the interest in ROCK signaling in normal physiology and disease, this mouse line will facilitate research into the consequences of ROCK activation that could be used to complement conditional knockout models. Birth Defects Research (Part A) 106:636–646, 2016. © 2016 Wiley Periodicals, Inc.